New Lithological Mapping of the Pantasma Impact Structure and Surroundings (Nicaragua) - Castro-Hidalgo , Darling F. (2026)
The Pantasma crater is a complex impact structure characterized by a clearly defined circular rim at 14 km, which is easily discernible in topographic maps. The presence of an outer rim has been identified, located 20 km from the geometric center of the crater. This study aims to assess the lithological environment and infer the location of structural rims to provide an updated lithological framework for the region. The methodology is based on the integration of terrestrial and satellite geological and geophysical records, allowing for the correlation of both parameters and the definition of the corresponding geological setting. Proximal and distal flow materials were identified and associated with monomict megabreccia impactites and polymict breccias containing altered melt fragments (suevite-type). A negative magnetic signature was also detected, associated with impact-induced demagnetization. Furthermore, inversions provided density contrasts related to high-density impactites. Therefore, this work provides a new lithological map of the crater, resolving interpretative ambiguities that support its genesis as an impact structure.